PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN DAN KEBUDAYAAN PESISIR SELATAN - Windy Desriliani; Henryanto Abaharis (LP2M Universitas Bina Bangsa, 2024)
This research aims to analyze the influence of leadership style, work motivation and work discipline on employee performance. This research was conducted by the South Pesisir Education and Culture Office. The sample in this research was all employees, totaling 54 respondents. This research is quantitative research and the data analysis method uses multiple linear regression. The results of this research show that the leadership style variable has a positive and significant influence on employee performance at the Pesisir Selatan Education and Culture Service, work motivation has a positive and significant influence on employee performance at the Pesisir Selatan Education and Culture Service, and work discipline has a positive and significant influence significantly to the performance of employees at the Pesisir Selatan Education and Culture Service, with each calculated t value being greater than the t table and the significant value being smaller than alpha. The conclusion is that the first hypothesis is accepted, the second hypothesis is accepted and the third hypothesis is accepted